Eine empirische Analyse der Internetnutzungsintensität in der deutschen Landwirtschaft; An Empirical Study of Internet Use Intensity in German Agriculture - Marius Michels; Wilm Fecke; Jan-Henning Feil; Oliver Mußhoff; Johanna Pigisch; Saskia Krone (German Journal of Agricultural Economics (GJAE), 2019)
– The internet plays a promising role for the future development of rural areas and offers several potential business relevant applications for agricultural entrepreneurs. Yet, little is known about the determinants of internet use intensity of German farmers. Thus, this paper empirically explores factors affecting internet use intensity in German agriculture using a representative data set collected in 2016. The representative data were analyzed using an ordered probit model. The results indicate that age, education, farm size and farm location play a statistical significant role. Moreover, our results show that farmers, who feel informed about dangers of the web, are more likely to be frequent internet user. Our results can be of interest for both policy makers and providers since they offer first insights into the determinants of German farmers' internet use intensity and, thus, provide hints for potential improvements in this area.
Keywords: 330